Media and Air Pollution Management, Policy and Legislation in Nigeria - Eric Msughter Aondover; Omotola Ogunbola; Omolara Oluwabusayo Akin-Odukoya; Ololade Olatunji Lateef; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
Air pollution is an acute problem in developing countries, especially their cities. In Nigeria the sources include vehicle exhaust aggravated by the rising car population, industrial emission, especially from petrochemical industries and cement manufacture, use of gasoline generation as a result of unstable power supply, use of fuel wood for domestic use and energy for small industries. This paper reviews air pollution and control measures in Nigeria. Data for the study was generated through secondary sources. The study discovered that it has been difficult to achieve cooperation for air pollution control in developing countries like Nigeria whose main concern is to provide for the basic needs as food, shelter and employment for her populace. The control measures have not been very effective and fully enforced. This paper therefore proposed preventive measures and sustainable solutions, such as vehicle inspection, enforcement of legislations, effective refuse collection and evacuation and steady supply of electricity to stop use of gasoline generators among others to ensure safe environment for the population to live.